Relationship Between Work Loads And Working Conditions With Nursing Stress Levels In Intensive Care Unit - Edison Siringoringo; Andi Susilawani; lhamsyah (Comprehensive Health Care, 2020)
Nurse workload is all activities carried out by nurses while on duty in a nursing service unit. Working conditions include physical environment variables such as the distribution of working hours, physical conditions in the form of noise, regulations, and demands. Job stress is a condition of tension that causes an imbalance of physical and psychological conditions in employees sourced from individuals and organizations that affect the physical, psychological, behavior of employees. This research method uses analytic research, with a cross-sectional design. The population in this study were nurses on duty in the ICU. The sample in this study amounted to 36 respondents with a sampling technique using the total sampling method. Data is collected by using a questionnaire sheet. Analysis of the data used by using the Chi-Square test. In this study, the results were obtained that the workload was in the bad category of 20 respondents (55.6%) and the working conditions included in the category did not support as many as 22 respondents (61.1%) and the stress level in the moderate category there were 23 respondents (63, 9%). Based on the analysis that has been done using the Chi-Square test, there is a significant relationship between workload with stress levels with a value of P = 0.000 <0.05 and work conditions with nurses' stress levels with a value of P = 0.011 <0.05. There is a relationship between workload and working conditions with the stress level of nurses in the ICU. It is hoped that this research can be used as additional knowledge for the educational institutions of Stikes Panrita Husada Bulukumba.